Pre-calculus Questions from Nov 10,2024

Browse the Pre-calculus Q&A Archive for Nov 10,2024, featuring a collection of homework questions and answers from this day. Find detailed solutions to enhance your understanding.

error msg
Find the horizontal asymptote, if any, of the graph of the rational function. \( g(x)=\frac{12 x^{2}}{4 x^{2}+3} \) Find the vertical asymptotes, if any, and the values of \( x \) corresponding to holes, if any, of the graph of the rational function. \( -h(x)=\frac{x+3}{x(x+8)} \) Follow the seven step strategy to graph the following rational function, \( f(x)=\frac{4 x^{2}}{x^{2}-4} \) point(s) posilble Find the horizontal asymptote, if any, of the graph of the rational function. \( g(x)=\frac{24 x^{2}}{6 x^{2}+1} \) A. The horizontal asymptote is B. There is no horizontal asymptote. (Type an equation.) Find the horizontal asymptote of the given functio \( g(x)=\frac{x^{2}+1 x-9}{x-9} \) Approximate the coordinates of each turning point by graphing \( f(x) \) in the standard viewing rectangle. \( f(x)=-7 x^{2}+13 x-5 \) Find the horizontal asymptote of the given function. \( g(x)=\frac{x^{2}+4 x-5}{x-5} \) Solve for \( x \) and leave your answer in \( \ln \) format \( 3 \sinh ^{2} x-2 \cosh x=2 \) 16. Prove by mathematical induction that, for all positive integers \( n \) (a) \( 1+3+5+\ldots+(2 n-1)=n^{2} \) (b) \( \frac{1}{1 \cdot 2}+\frac{1}{2 \cdot 3}+\frac{1}{3 \cdot 4}+\ldots+\frac{1}{n(n+1)}=\frac{n}{(n+1)} \) (c) \( 1^{3}+2^{3}+3^{3}+\ldots+n^{3}=\left[\frac{1}{2} n(n+1)\right]^{2} \) (d) \( 3+11+\ldots+(8 n-5)=4 n^{2}-n \) (e) \( \frac{1}{1 \cdot 2 \cdot 3}+\frac{1}{2 \cdot 3 \cdot 4}+\ldots+\frac{1}{n(n+1)(n+2)}=\frac{n(n+3)}{4(n+1)(n+2)} \) (f) \( 1 \cdot 2 \cdot 3+2 \cdot 3 \cdot 4+\ldots+n(n+1)(n+2)=\frac{n(n+1)(n+2)(n+3)}{4} \) (g) \( 1+2+2^{2}+\ldots+2^{n-1}=2^{n}-1 \) (h) \( 1 \cdot 3+2 \cdot 3^{2}+4 \cdot 3^{3}+\ldots+n \cdot 3^{n}=\frac{(2 n-1) 3^{n+1}+3}{4} \) 16. Prove by mathematical induction that, for all positive integers \( n \) (a) \( 1+3+5+\ldots+(2 n-1)=n^{2} \) (b) \( \frac{1}{1 \cdot 2}+\frac{1}{2 \cdot 3}+\frac{1}{3 \cdot 4}+\ldots+\frac{1}{n(n+1)}=\frac{n}{(n+1)} \) (c) \( 1^{3}+2^{3}+3^{3}+\ldots+n^{3}=\left[\frac{1}{2} n(n+1)\right]^{2} \) (d) \( 3+11+\ldots+(8 n-5)=4 n^{2}-n \) (e) \( \frac{1}{1 \cdot 2 \cdot 3}+\frac{1}{2 \cdot 3 \cdot 4}+\ldots+\frac{1}{n(n+1)(n+2)}=\frac{n(n+3)}{4(n+1)(n+2)} \) (f) \( 1 \cdot 2 \cdot 3+2 \cdot 3 \cdot 4+\ldots+n(n+1)(n+2)=\frac{n(n+1)(n+2)(n+3)}{4} \) (g) \( 1+2+2^{2}+\ldots+2^{n-1}=2^{n}-1 \) (h) \( 1 \cdot 3+2 \cdot 3^{2}+4 \cdot 3^{3}+\ldots+n \cdot 3^{n}=\frac{(2 n-1) 3^{n+1}+3}{4} \) 17. Prove \( u s i n g \) mathematical induction that for any positive integer \( n \) (a) \( a^{n}-b^{n} \) is divisible by \( a-b \) (b) \( a^{2 n-1}+b^{2 n-1} \) is divisible by \( a+b \) (c) \( (a b)^{n}=a^{n} b^{n} \) for \( a>0 \) (d) \( \left(\frac{a}{b}\right)^{n}=\frac{a^{n}}{b^{n}} \) (e) \( n^{3}+5 n \) is divisible by 3 (f) \( 5^{n}-1 \) is divisible by 4 (a) \( A^{n}-1 \) is divisible bu 3
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy